The Impact of Globalization on the Renewal of Islamic Education - Anis Zohriah; Al Farisi, Fazrurrakhman; Rijal Firdaos (Journal of Islamic Civilization, 2024)
Globalization has changed the world rapidly, including Islamic learning. Therefore, this post identifies and analyzes globalization's positive and negative effects on Islamic learning updates. Literature review procedures are used in this article to collect information from reliable sources, such as academic newspapers, novels, and scientific articles related to the impact of globalization on Islamic learning. From the results of the literature review, there are some positive and negative effects of globalization on Islamic learning updates. The positive effects of globalization on Islamic learning updates include increasing access to data and knowledge through technology, expanding the curriculum to include scientific research and modern technology, and increasing women's participation in Islamic learning. Not only that, but globalization also poses challenges that have forced the Muslim world to reform Islamic education so that it fits the changing times and the needs of society. However, the adverse effects of globalization also appear in Islamic learning updates. One of the significant negative consequences is the possibility of Western cultural influences that can interfere with the Islamic values ​​and traditions of Muslim citizens. Another negative consequence is the formation of neglect of aspects of spirituality in Islamic learning due to the influence of secular and materialistic thinking. This post concludes that globalization has had a significant impact on updating Islamic knowledge. The positive effects of globalization have opened opportunities for updating Islamic learning by incorporating data technology into the curriculum, expanding the field of research, and increasing women's participation in Islamic knowledge. However, the negative consequences of globalization such as the influence of Western culture and the neglect of aspects of spirituality in Islamic learning must be handled carefully and wisely.